Kajian Lafaz 'Ām dan Khāṣ dalam Ushul Fikih serta Implikasinya terhadap Penetapan Hukum Islam - Musliadi; Abdul Syatar; Fatmawati (AHKAM, 2026)
Although the concepts of ‘ām and khāṣ expressions have been widely discussed in the literature on Ushul Fiqh, studies comprehensively analyzing their implications for the process of Islamic legal determination remain relatively limited. This study aimed to analyze the concepts of ‘ām and khāṣ expressions, the forms of their use in the texts of the Qur’an and Hadith, and their implications for the process of Islamic legal istinbāṭ. The study employed a qualitative approach using library research. Data were obtained through a documentation study of Ushul Fiqh texts, Qur’anic exegesis texts, books, and relevant scholarly journal articles and were subsequently analyzed using descriptive-analytical and content analysis methods. The findings showed that ‘ām expressions contain a general scope of legal application, whereas khāṣ expressions restrict the applicability of a law to certain objects, individuals, or conditions. The mechanism of takhṣīṣ serves to restrict the generality of an expression, thereby producing a more precise and proportional legal interpretation that is aligned with the objectives of Sharia. Understanding the relationship among ‘ām, khāṣ, and takhṣīṣ expressions also has important implications for the consistency and accuracy of the process of Islamic legal istinbāṭ. This study concludes that mastery of linguistic principles concerning general and specific expressions is an essential element in determining Islamic law methodologically. These findings contribute to the development of Ushul Fiqh studies, particularly by strengthening the methodology of Islamic legal determination based on linguistic analysis of Sharia sources. Keywords: Ushul Fiqh; ‘Ām Expressions; Khāṣ Expressions; Takhṣīṣ; Legal Istinbāṭ